Integrated Geophysical and Geotechnical Approaches for Evaluating Dam Seepage in Lesser Himalayan Region of Pakistan - Umair Bin Nisar; Muhammad Farooq; Sarfraz Khan; Ramesh Raj Pant; Iftikhar A. Satti; Ali Wahid; Faizan ur Rehman Qaiser; Syed Amjad Ali Bukhari; Furqan Mahmud Butt (Geofluids)
Dam leakage is a major problem in earth-filled reservoir dams. The present research is aimed at detecting the seepage zones in an earth-filled reservoir dam in the vicinity of Sarobi village, North Waziristan, Pakistan. The objective was achieved by integrating geological, geotechnical, and geophysical datasets. Geological survey was carried out in the area to identify the surface exposures. Geotechnical data involved was used to estimation of permeability and Lugeon values to identify network of joints/fractures whereas electrical resistivity tomography (ERT) technique (utilizing Wenner-Schlumberger configuration) was applied for the identification of the leakage zones. Geological data revealed highly deformed alluvium towards the right abutment underlain by compressed shale and highly fractured limestone beds. Geotechnical data indicated high permeability, Lugeon values, and concentration of sand and gravel towards the right abutment whereas low permeability, Lugeon values, and higher concentration of silt and clay were observed towards the left abutment. ERT data identified a conductive zone embedded between impermeable lithologies having resistivity between 10 and 60 Ω·m. This conductive zone was observed in parallel profiles acquired in upstream, dam crest, and downstream parts of the dam. The integration of all the datasets revealed a network of joints that are interconnected and provide a path for water at the upstream side to pass through right abutment of dam and leak towards the downstream.